Phytochemical investigation of the tomatillo fruit (Physalis ixocarpa Brot., Solanaceae) - K. Drost-Karbowska; M. Ellnain-Wojtaszek; A. Gawron-Gzella; Z. Kowalewski; L. S. Jankiewicz; I. Matławska; M. Sikorska; M. Szaufer-Hajdrych; A. Walkowiak (Acta Societatis Botanicorum Poloniae, 2014)
The occurence of alkaloids, witanolides, saponosides and flavonoids was investigated in the fruits of tomatillo (Physalis ixocarpa Brot.) cv. Bujna and Rendidora. The tomatillo is commonly cultivated in Mexico and has been introduced on a small scale in Poland. The chromatographic analysis of alkaloids showed only trace amounts of compounds reacting with the Dragendorff reagent. In the fraction of quaternary alkaloids soluble in water, only choline was found. Witanolides were not detected in tomatillo fruits. The saponosides were found only in trace amounts and their hemolytic indexes as well as saponification numbers were very low. Flavonoids were represented by the derivatives of quercetine differring with their sugar moieties attached to the hydroxyl group at C-3. It is concluded that the toxic compounds which would be harmful to human health were not found in tomatillo fruits. The presence of choline in them, as well as of flavonoids belonging to the vitamin P group is advantageous for health.